15 Post-operative hypotension in fractured neck of femur: the role of the high dependency unit. (16th November 2020) - Walker, Patrick; King, Oliver; Harris, Stephen
Abstract : Patients with a fractured NOF (Neck of Femur) present multiple challenges perioperatively. Since 2014, 11 major events were identified as poor or incorrect postoperative management of hypotension at Musgrove Park Hospital. This improvement project looked to implement a framework for recovery and medical staff to use in the management of post-operative hypotension. A retrospective review was undertaken of 22 patients following fractured NOF surgery in November 2018. This found 50% (11/22) of patients had one or more episodes of post-operative hypotension (Systolic < 100 mmHg), two patients had ongoing blood pressure (BP) support in recovery but only one was escalated to HDU. The patient not admitted developed an AKI day 1 post op. We then implemented an algorithm in orthopaedic recovery to guide healthcare workers through initial treatment options for post-operative hypotension and a time frame for referral to HDU. Data was collected prospectively from March 2019 to March 2020 to assess impact on HDU bed capacity, patient outcomes, post-operative AKI, length of hospital stay and time to first mobilisation. 4.8% (24/493) of patients were admitted to HDU with a fractured NOF. 18 were admitted with refractory hypotension for ongoing BP support. The incidence of post-operative hypotension in patients reduced from 14.3% to 4.7% in patients transferred back to the ward and 0/18 patients admitted to HDU had an AKI. 3 patients who were initially transferred to the ward were also admitted and one developed a post-operative AKI. No improvement was found in first mobilisation and length of stay. A review of critical care bed capacity found there was no impact on admissions after elective surgery. Implementation of this pathway has reduced incidence of post-operative hypotension and AKI. Demonstrating that enhanced post-operative care can have a role in fractured NOF management with minimal impact on critical care bed capacity.